2019
DOI: 10.1111/1365-2656.13122
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in age‐dependent reproduction: Fast explorers live fast but senesce young?

Abstract: Adaptive integration of life history and behaviour is expected to result in variation in the pace‐of‐life. Previous work focused on whether ‘risky’ phenotypes live fast but die young, but reported conflicting support. We posit that individuals exhibiting risky phenotypes may alternatively invest heavily in early‐life reproduction but consequently suffer greater reproductive senescence. We used a 7‐year longitudinal dataset with >1,200 breeding records of >800 female great tits assayed annually for exploratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 72 publications
0
47
0
Order By: Relevance
“…For example, an increasingly popular approach is to determine the relative fit of alternative SEMs based on the entire posterior distribution (rather than the point estimates) of among individual (Araya‐Ajoy & Dingemanse, 2014) or genetic correlation matrices (e.g., Dingemanse, Barber, et al, 2020; Dochtermann & Dingemanse, 2013). Such solutions are welcome, but can introduce their own biases and are therefore best used in combination with simulations that demonstrate their utility for the particular data set at hand (e.g., Araya‐Ajoy & Dingemanse, 2017; Dingemanse, Moiron, Araya‐Ajoy, Mouchet, & Abbey‐Lee, 2020; Dochtermann & Dingemanse, 2013). Again, simpler pragmatic solutions are acceptable, but authors should always be clear about their different options, how any issues related to stats‐on‐stats were dealt with, and how those decisions might affect their biological conclusions.…”
Section: Statistical Analyses and Reporting Resultsmentioning
confidence: 99%
“…For example, an increasingly popular approach is to determine the relative fit of alternative SEMs based on the entire posterior distribution (rather than the point estimates) of among individual (Araya‐Ajoy & Dingemanse, 2014) or genetic correlation matrices (e.g., Dingemanse, Barber, et al, 2020; Dochtermann & Dingemanse, 2013). Such solutions are welcome, but can introduce their own biases and are therefore best used in combination with simulations that demonstrate their utility for the particular data set at hand (e.g., Araya‐Ajoy & Dingemanse, 2017; Dingemanse, Moiron, Araya‐Ajoy, Mouchet, & Abbey‐Lee, 2020; Dochtermann & Dingemanse, 2013). Again, simpler pragmatic solutions are acceptable, but authors should always be clear about their different options, how any issues related to stats‐on‐stats were dealt with, and how those decisions might affect their biological conclusions.…”
Section: Statistical Analyses and Reporting Resultsmentioning
confidence: 99%
“…Un-banded birds were given a unique, numbered band. Birds were then tested for their exploratory behaviour (detailed below), weighed, morphologically measured (Moiron et al 2019), aged based on plumage characteristic as first year breeder or older (Dingemanse et al 2020), and assessed for ticks (protocol detailed below). All birds were captured in May (with a few captures in June in 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The usage of BLUPs has been criticised when associated uncertainty is not taken forward; some have proposed to estimate a posterior distribution of possible BLUP values and thereby take forward uncertainty in subsequent analyses (Hadfield et al 2010; Houslay and Wilson 2017). However, recent work has shown that taking forward uncertainty in BLUP-values resulted in biased estimates, whereas utilizing average BLUPs as fixed effects was shown to be less precise but unbiased (Dingemanse et al 2020). Therefore, we here present the estimated effect of the average BLUP values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many organisms, reproductive productivity is age-dependent (Bouwhuis et al, 2009;Hammers et al, 2012;Lemaître et al, 2015;Zhang et al, 2015;Salguero-Gómez et al, 2016;Jankowiak et al, 2018;Dingemanse et al, 2020): an individual's performance increases over early life to a maximum and is followed by a decline in older ages. This decline in reproductive performance at old age is considered a sign of senescence -a within-individual age-specific decline in reproductive performance paired with an increase in the probability of death caused by the loss of physiological and cellular function (Medawar, 1952;Williams, 1957).…”
Section: Impact Summary (297 Words)mentioning
confidence: 99%